Superiority of the Lyon schuss view over the standing anteroposterior view for detecting joint space narrowing, especially in the lateral tibiofemoral compartment, in early knee osteoarthritis. Issue 6 (16th January 2007) - Merle-Vincent, F; Vignon, E; Brandt, K; Piperno, M; Coury-Lucas, F; Conrozier, T; Mathieu, P; Hellio Le Graverand, M P
Abstract : Objective: To evaluate the validity of using the conventional anteroposterior (AP) radiograph of the knee in order to identify joint space narrowing (JSN) at an early stage of osteoarthritis (OA). Methods: Grading of JSN using a 0–5 score and quantitative measurement of joint space width (JSW) of the medial and lateral compartments of the tibiofemoral joint in AP and fluoroscopically assisted posteroanterior Lyon schuss (LS) radiographs of 202 patients with knee OA. Results: Knees without definite JSN (score <2) were twice as common in AP than in LS radiographs (36.1% vs 18.8%). The number of knees showing definite medial JSN was identical in both views but four knees showing a medial OA in AP view were classified differently in the LS radiographs (three bicompartmental OA and one lateral OA). The frequency of lateral JSN was approximately twice as great in the LS view as in the AP view. JSN score was significantly higher (p<0.001) and JSW was significantly smaller (p<0.01) in the LS view than in the AP view. In knees with definite JSN, JSW of the compartment with no narrowing was significantly (p<0.04) larger than in knees that did not exhibit definite JSN. Medial JSW and lateral JSW were inversely correlated (p<0.001). Conclusions: The standing AP radiograph performed poorly in identifying both the location of JSN in patients with early tibiofemoral OA (especially, lateral OA) and the severity of JSN. The LS radiographs are preferable to standing AP views for the selection of patients for therapeutic trials of structure-modifying OA drugs.